Constructing three emotion knowledge tests from the invariant measurement approach - Delgado, Ana R. (2017)
Background. Psychological constructionist models like the Conceptual Act Theory (CAT) postulate that complex states such as emotions are composed of basic psychological ingredients that are more clearly respected by the brain than basic emotions. The objective of this study was the construction and initial validation of Emotion Knowledge measures from the CAT frame by means of an invariant measurement approach, the Rasch Model (RM). Psychological distance theory was used to inform item generation. Methods. Three EK testsemotion vocabulary (EV), close emotional situations (CES) and far emotional situations (FES)were constructed and tested with the RM in a community sample of 100 females and 100 males (age range: 18-65), both separately and conjointly. Results. It was corroborated that data-RM fit was sufficient. Then, the effect of type of test and emotion on Rasch-modelled item difficulty was tested. Significant effects of emotion on EK item difficulty were found, but the only statistically significant difference was that between "happiness" and the remaining emotions; neither type of test, nor interaction effects on EK item difficulty were statistically significant. The testing of gender differences was carried out after corroborating that differential item functioning (DIF) would not be a plausible alternative hypothesis for the results. No statistically significant sex-related differences were found out in EV, CES, FES, or total EK. However, the sign of d indicate that female participants were consistently better than male ones, a result that will be of interest for future meta-analyses. Discussion. The three EK tests are ready to be used as components of a higher-level measurement process.